2023
DOI: 10.1007/s00394-023-03135-7
|View full text |Cite
|
Sign up to set email alerts
|

Shifting towards optimized healthy and sustainable Dutch diets: impact on protein quality

Abstract: Purpose To reduce the environmental impact of Western diets, a reduction of meat consumption and a substitution by plant-based protein sources is needed. This protein transition will affect the quantity and quality of dietary protein. Therefore, the aim of this study was to evaluate the protein adequacy of diets optimized for nutritional health and diet-related greenhouse gas emission (GHGE). Methods Data from 2150 adult participants of the Dutch National… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…This focus is also applicable to low-income countries where current diets suffer from nutrient inadequacy (Han et al, 2022). In this regard, some studies have shown that there is a point to which health and environmental impact can be improved simultaneously when current diets are far for optimal, while the trade-offs between health and environment appear mainly when it comes to marginal changes within diets (Stylianou et al, 2021;Heerschop et al, 2023). Moreover, the synergic environmental and health benefit from a reduction of animal source foods is also dependent on the functional unit used, e.g., water use in our study is relatively high for 100 kcal of fruits and vegetables, and will even be higher when expressed on protein content, but when expressed on a mass base, these food groups perform relatively well (Sokolow et al, 2019).…”
Section: Identifying Trade-offs In Healthy and Sustainable Food Consu...mentioning
confidence: 99%
“…This focus is also applicable to low-income countries where current diets suffer from nutrient inadequacy (Han et al, 2022). In this regard, some studies have shown that there is a point to which health and environmental impact can be improved simultaneously when current diets are far for optimal, while the trade-offs between health and environment appear mainly when it comes to marginal changes within diets (Stylianou et al, 2021;Heerschop et al, 2023). Moreover, the synergic environmental and health benefit from a reduction of animal source foods is also dependent on the functional unit used, e.g., water use in our study is relatively high for 100 kcal of fruits and vegetables, and will even be higher when expressed on protein content, but when expressed on a mass base, these food groups perform relatively well (Sokolow et al, 2019).…”
Section: Identifying Trade-offs In Healthy and Sustainable Food Consu...mentioning
confidence: 99%
“…Other approaches circumvent this problem by considering a priori defined omnivorous, vegetarian, or vegan dietary regimens ( 69 ). More recent models addressed food preference, food choice, and cultural acceptability by incorporating costs ( 70 , 71 ), taste, and texture ( 72 ), constraining the deviation from current dietary patterns ( 73 ), or making linear combinations of whole diets ( 68 , 74 ). Approaches that rely on currently existing dietary patterns have the advantage of realism and greater acceptability; conversely, however, they cannot identify radically different solutions that go beyond the current food consumption, composition, and production system.…”
Section: Diets and Food Systemsmentioning
confidence: 99%
“…In comparison to foods from animal sources, plant-based foods such as legumes, nuts, and plant-based alternatives are typically low in saturated fats and rich in unsaturated fatty acids, dietary fiber, and phytonutrients such as polyphenols [14]. A (partial) replacement of animal products with plant-based foods may provide beneficial health outcomes, such as a reduced risk of type II diabetes, cancer, coronary heart disease, and premature mortality [12,15,16]. Plant-based foods also generally provide more thiamin, vitamin C, Nutrients 2023, 15, 2473 2 of 14 folate, and potassium than animal products [15].…”
Section: Introductionmentioning
confidence: 99%
“…A (partial) replacement of animal products with plant-based foods may provide beneficial health outcomes, such as a reduced risk of type II diabetes, cancer, coronary heart disease, and premature mortality [12,15,16]. Plant-based foods also generally provide more thiamin, vitamin C, Nutrients 2023, 15, 2473 2 of 14 folate, and potassium than animal products [15]. On the other hand, animal foods are essential sources of macro-and micronutrients that are difficult to obtain from plant-based foods [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation